Estimation Of The Value Of Goods And Services Produced By Protected Areas: Case Of The Ndock Sare Community Forest In Senegal - Mamadou Ndiaye; Saboury Ndiaye; Sérigne Modou Sarr; Malick Diouf (European Scientific Journal, ESJ, 2021)
The community forests of Senegal, and particularly those of the Groundnut Basin, play an important role in the lives of rural populations. They are significant sources of supply of various products and services. But despite their economic and ecological importance, community forests have never been the subject of an economic evaluation. This is likely to obscure the decision-making auspices of sustainable management of community forests. This study, based on vegetation surveys and socio-economic surveys, assessed the value of ecosystem goods and services. The results of the analysis showed that the forest has 21 species distributed among 08 families and that this diversity varies from one area to another. With this specific diversity, the basal area is evaluated at 2.64 m2/ha and the cover of 6081.17 m²/ha for a density of 327 individuals per hectare. The forest has a carbon storage capacity evaluated at 15.32 tons. The goods and services of the forest were estimated at 3,391,757 F CFA/year. This value is divided between direct uses estimated at 1,236,575 F CFA/year, indirect uses of 168,495 F CFA/year and an existence value of 1,986,687 F CFA/year. The study also showed that the exploitation of the forest is the most viable management option, as strict conservation imposes a social cost of 370,058 CFA francs per year on the population. In the context of decentralization, these results can serve as a basis for policy dialogue and decision-making processes on the sustainable management of forest resources